Effect of a specific food intervention with Tamogitake mushroom, Moringa leaves, or rice bran on intestinal microbiota and cognitive function in elderly Japanese - Kouta Hatayama; Kanako Kono; Kana Okuma; Hiroaki Masuyama (Frontiers in Nutrition)
IntroductionThe large number of elderly patients with dementia and mild cognitive impairment with cognitive decline in Japan has become a social problem. In this study, a food intervention study was conducted to test whether a food intervention approach targeting intestinal microbiota can improve cognitive function in elderly Japanese individuals.MethodsJapanese participants (144 males and 87 females) aged 60–79 years were assigned to one of the test food groups: Tamogitake mushroom (Pleurotus cornucopiae var. citrinopileatus), Moringa oleifera Lam. leaves, and rice bran for each sex, respectively. After 4 weeks of pre-observation, each group consumed the test foods for 8 weeks; cognitive function and intestinal microbiota tests were performed after each 4-week period. The intestinal microbiota of each participant was determined by 16S rRNA gene amplicon sequencing.ResultsThe participants were divided into responders (improved cognitive function) and non-responders (no improvement) within each sex group. Responders exhibited variations in intestinal bacteria belonging to specific taxa, including Agathobaculum, Anaerobutyricum, Blautia, Faecalibacterium, Parabacteroides, and Phascolarctobacterium, compared to non-responders, indicating that cognitive function may be improved by changes in specific intestinal bacteria with food intake. However, improvements in cognitive function would require consuming foods suitable for the composition of the intestinal microbiota.ConclusionFood intervention approaches targeting the intestinal microbiota could lead to innovative solutions for improving cognitive function in the elderly.